AQUA: A blockchain based multi-winner e-voting system - Karanikolas, Nikos; Kaklamanis, Christos; Nikolopoulos, Stefanos (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Conducting fair and secure elections has been the heart of democracy since its birth in ancient Greece. To be more precise, the act of voting has been an essential and significant component of human societies, particularly for government and municipal elections. Nonetheless, the conventional method of casting a ballot by physically visiting a voting booth raises concerns regarding the security of the process, as there have been reported incidents of tampering. To tackle these issues, we propose an online voting system that makes use of Blockchain technology. By utilizing encryption and hashing techniques, the Blockchain system guarantees the security of each vote. In our proposed system, a smart contract is triggered when an election is scheduled, thereby facilitating a secure and efficient voting process. The need to modernize voting systems has become more urgent due to the increasing frequency and volume of voters. Despite these challenges, security and fairness should not be compromised. Therefore, modernizing voting systems in terms of security is essential to ensure the integrity of elections, so that voters can have confidence in the electoral process. To address this challenge, we introduce Aqua, a distributed system that implements a multi-winner approval-based voting scheme, following the AV rule, on the Ethereum blockchain. Aqua supports both English and Greek languages for multi-winner elections with committee sizes up to three members. It is user-friendly, cost-effective, and accessible from any device with an Internet connection. Aqua voting is based on the AV rule, but it can be readily modified to accommodate any multi-winner voting scheme with any committee size.